Outbreak and Persistence of Mareks Disease in Batches of Birds Reared in a Poultry Farm Located in Nsukka, South East Nigeria - Okwor, E.C.; Eze, D.C. (International Journal of Poultry Science, 2011)
Marek’s Disease (MD) is an important viral disease that has been described in Nigeria. Though poultry farmers may not be familiar with the disease when compared to other common diseases like Newcastle Disease (ND) and Infections Bursal Disease (IBD) sporadic outbreaks of this disease occurs in poultry farms resulting in significant economic losses. This work investigated an outbreak and persistence of MD in batches of birds reared in a poultry farm in Nsukka, South East Nigeria between 2001 and 2009. The farm maintains many pens situated close to each other and introduces birds of different ages thereby housing different batches of birds throughout the year. The first outbreak occurred in a batch of 300 brown pullets at the age of 12 weeks. Infection occurred in all the subsequent batches of pullets introduced into the farm within the study period. Batches of broilers introduced into the farm and kept up to six weeks and above had the infection. Those that were sold before six weeks of age as brooded birds did not show signs of MD. Cockerels that were kept and reared to maturity showed signs of the disease while those that were reared and sold as brooded birds at four-five weeks did not show signs of the disease. In most cases, infection among the flock (morbidity) varied ranging from 5-15% with few acute cases up to 25%. We therefore suggested an ‘all-in-all-out’ system in case of outbreaks of the disease with reasonable period or interval between each stock.